1996
DOI: 10.1111/j.1540-8159.1996.tb03218.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Pacing for End‐Stage Heart Failure: Early Experience

Abstract: Our objective was to improve hemodynamics by synchronous right and left site ventricular pacing in patients with severe congestive heart failure (CHF). Previous studies reported a benefit of dual chamber pacing with a short AV delay in patients with severe CHF. Other works, however, show contradictory results. Deleterious effects due to a desynchronization of right (RV) and left ventricular (LV) contractions have been suggested. This study included eight subjects with widened QRS and end-stage heart failure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
0
14

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(188 citation statements)
references
References 13 publications
4
170
0
14
Order By: Relevance
“…[1][2][3][4][5] By providing early stimulation to the otherwise late-activated region, pacing probably improves contractile coordination to enhance ejection. However, the therapy involves an implantable device, making it important to identify patients most likely to benefit.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] By providing early stimulation to the otherwise late-activated region, pacing probably improves contractile coordination to enhance ejection. However, the therapy involves an implantable device, making it important to identify patients most likely to benefit.…”
mentioning
confidence: 99%
“…Various studies have demonstrated efficacy of biventricular pacing in advanced heart failure [2,3,7]. The acute hemodynamic improvement was also observed in the immediate postoperative course in patients undergoing open heart surgery with impaired left ventricular function [4-6].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients resynchronization of the interventricular conduction system by biventricular stimulation leads to improvement of quality of life and NYHA (New York Heart Association) class [2,3]. In open heart operations the acute hemodynamic benefit of biventricular pacing can be used by implantation of temporary epicardial electrodes facilitating weaning from extracorporeal circulation in high risk patients with impaired left ventricular function and improving cardiac output postoperatively [4-6].…”
Section: Introductionmentioning
confidence: 99%
“…Hedef dal küçük veya büyük olsun içerisindeki stylet veya guidewire çıkarıldığı zaman kıvrıntılı şekil alarak dal duvarına birkaç noktadan dayanan elektrodlar tercih edilmelidir. Çok büyük damarlar için geliştirilmiş özel fiksasyon sistemli elektrodlar bulunmaktadır (Şekil 13) [1,3,4,11]. …”
Section: Sol Ventrikül Elektrodu Yerleştirme Teknikleriunclassified